COMPETITION ANALYSIS OF THE PUBLIC INSURANCE INDUSTRY IN INDONESIA - Nabila Natasha (Universitas Gunadarma, 2022)
This study aims to analyze the general insurance industry competition in Indonesia. The research method uses a qualitative descriptive approach. This research was conducted at one of the general insurance companies in Indonesia. Data collection techniques were carried out by interview and questionnaire methods. Determination of research respondents using an expert sampling technique. The analytical approach used is Porter’s five forces analysis developed by Michael Porter. The analysis results show that all five variables of Porter’s power affect the general insurance industry. The variable threat of new entrants has a powerful influence on the general insurance industry. To win the competition in the industry, insurance companies can develop existing products or new products according to the needs of consumers. Companies can also build employee capabilities to minimize the role of brokers in the business.